PENGARUH PENGGUNAAN E-MODUL INTERAKTIF TERHADAP HASIL BELAJAR SISWA KELAS XI PADA MATERI GELOMBANG BUNYI - Puspita, Windi; Rosa, Friska Octavia; Alarifin, Dedy Hidayatullah (JURNAL FIRNAS, 2023)
Abstract: This study aimed to determine the effect of using interactive 3D Emodules on learning outcomes on sound wave material for class IX MA Muhammadiyah Metro for the 2021-2022 academic year. This research used a quantitative approach with a type of quasi-experimental research using Non Equivalent Control Group. The data collection technique used the written test method. The test instrument used was a multiple choice test in the form of a posttest which amounted to 10 multiple choice questions. The population in this study were all 9th grade students of MA Muhammadiyah Metro. The target of this study were students of class XI Al-Hikmah as many as 20 people as an experimental class and class XI An-Nahl as many as 19 people as a control class. Sampling technique was by means of non probability sampling technique. The hypothesis test used was Independent Sample T-test and N-gain score test, which previously tested the prerequisites of normality and homogeneity. The results showed that: (1) based on the results of the Independent Sample T-test test, the Sig. (2-tailed) of 0.032, so it can be concluded that there was a significant effect of using interactive 3D E-modules on learning outcomes in sound wave material of class IX MA Muhammadiyah Metro students, (2) based on the results of the N-gain score test calculation above, it showed that the average value of the N-gain score for the experimental class (Interactive 3D E-Module) was 0.54 including in the medium or quite effective category. While the N-gain score for the control class (Conventional LKS) is 0.30 including in the low or ineffective category.